Comprehension of Basic Epidemiology Concepts Among Supervisors of Postgraduate Medical Trainees - Faisal, Tayyaba; Saleem, Sahrish; Haque, Ayesha; Obaid, Shumaila; Naseem, Sajida; Mangrio, Sana (Pakistan Armed Forces Medical Journal, 2025)
Objective: To study the comprehension of basic epidemiological concepts among supervisors of postgraduate medical trainees Study Design: Cross-sectional Analytical study. Place and Duration of Study: College of Physicians and Surgeons Pakistan Regional Center, Islamabad Pakistan from Oct 2021 to Mar 2022. Methodology: To assess postgraduate trainee supervisors’ comprehension of basic epidemiology in medical research. The supervisors of postgraduate trainees working in public and private tertiary care hospitals of Islamabad and Rawalpindi were enrolled in the study through consecutive non-probability sampling. A questionnaire comprising demographics and variables covering the concept of epidemiology from rationale writing to methodology was applied at the onset of the workshop. The total score was categorized into poor, average, and sound. Results: 260 supervisors were enrolled in the study, with a mean age of 28.2±2.5 years. Among the supervisors, 143(55%) were female, and 117(45%) were male. Regarding comprehension of epidemiology concepts, the majority of the supervisors, 201(77.3%), had average comprehension, 47(18.1%) had a good understanding, and 12(4.6%) had poor comprehension. The maximum number of supervisors correctly understood randomized controlled trials was 204 (78.5%). No statistically significant difference was observed between understanding of epidemiology with gender and specialty, p-value> 0.05. Conclusion: This study showed an average comprehension of epidemiology, which is not enough to train the postgraduate trainees in research and design quality studies sufficient to generate data at the local level for evidence-based practice.